Erratum: Moral Hazard versus Liquidity and Optimal Unemployment Insurance - Chetty, Raj (Journal of Political Economy, 2008)
Previous articleNext article FreeErratumErratum: Moral Hazard versus Liquidity and Optimal Unemployment InsuranceRaj ChettyRaj ChettyUniversity of California, Berkeley Search for more articles by this author University of California, BerkeleyOriginal articleMoral Hazard versus Liquidity and Optimal Unemployment InsurancePDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreIn the April 2008 issue of the Journal of Political Economy, there is an error on page 211. The last sentence of the first paragraph of Section IV.C should read: “As a result, 75 percent of individuals who received severance pay remain unemployed after 10 weeks, compared with 68 percent among those who received no severance payment.” In the original manuscript, the 68 percent and 75 percent were switched, and thus the statement was inconsistent with figure 5. I am grateful to Olaf Storbeck for pointing out this typographical error. Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 116, Number 6December 2008 Article DOIhttps://doi.org/10.1086/597025 Views: 743Total views on this site Citations: 1Citations are reported from Crossref © 2008 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Yolanda F. Rebollo-Sanz, J. Ignacio García-Pérez Are unemployment benefits harmful to the stability of working careers? The case of Spain, SERIEs 6, no.11 (Dec 2014): 1–41.https://doi.org/10.1007/s13209-014-0120-zRelated articlesMoral Hazard versus Liquidity and Optimal Unemployment Insurance19 Jul 2015Journal of Political Economy